Relation between School Environment Variables and Mathematics Achievement among School Students in Bongaigaon District - Patra, Kuntala; Mech, Arundhati (JOURNAL OF INDIAN EDUCATION, 2011)
This article focuses on differences in mathematics achievement among school students in Bongaigaon district of Assam. The researchers conducted a comparative study between the groups of students divided on basis of different school environment variables in order to study the variation of achievement in mathematics. Data came from the test scores of 580 secondary school children in Bongaigaon district. An analysis of data indicates that the school environment does have an impact on mathematics achievement. This indicates the important responsibility of schools towards providing equitable education to all sections of children especially in developing countries.